2017
DOI: 10.1152/japplphysiol.00873.2016
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects against uric acid-induced mitochondrial dysfunction, oxidative stress, and triglyceride accumulation in C2C12myotubes

Abstract: Excess uric acid has been shown to induce oxidative stress, triglyceride accumulation, and mitochondrial dysfunction in the liver and is an independent predictor of type-2 diabetes. Skeletal muscle plays a dominant role in type 2 diabetes and presents a large surface area to plasma uric acid. However, the effects of uric acid on skeletal muscle are underinvestigated. Our aim was therefore to characterize the effects of excessive uric acid on oxidative stress, triglyceride content, and mitochondrial function in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 47 publications
1
13
0
1
Order By: Relevance
“…The beneficial effects of UA as an antioxidant in bone health have been shown [41,42], but there are few studies addressing the direct effects of UA on muscle health. Recently, an in vitro study found that exogenous UA increased oxidative stress in C2C12 skeletal muscle cells [43]. Therefore, the exact mechanism underlying the positive association between SUA and ASMI remains unclear, and additional studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of UA as an antioxidant in bone health have been shown [41,42], but there are few studies addressing the direct effects of UA on muscle health. Recently, an in vitro study found that exogenous UA increased oxidative stress in C2C12 skeletal muscle cells [43]. Therefore, the exact mechanism underlying the positive association between SUA and ASMI remains unclear, and additional studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported in animal and human studies, showing decreased serum uric acid levels in asthma patients according to disease severity . The relationship between uric acid, the final product of purine metabolism, inflammation and oxidative stress remains controversial, with studies showing high uric acid concentrations inducing inflammation and oxidative stress, resulting in apoptosis . However, increasing studies showed uric acid as a candidate asthma‐specific biomarker based on its antioxidative roles in decreasing ROS and preventing oxidative damage .…”
Section: Discussionmentioning
confidence: 99%
“…Uric acid has been found to be strongly associated with triglycerides, regardless of age, sex, smoking, alcohol consumption, obesity and insulin resistance, in a study published in China 26 . Uric acid and triglyceride levels have also been linked to oxidative stress and mitochondrial dysfunction 27 , but there was also a decrease in the level of uric acid and triglycerides following the administration of glycine and tryptophan without diet therapy [28][29][30] .…”
Section: Discussionmentioning
confidence: 99%